2015
DOI: 10.1111/jfd.12425
|View full text |Cite
|
Sign up to set email alerts
|

First report and description of a Cyrilia sp. (Apicomplexa: Haemogregarinidae) from a freshwater Cururu Stingray Potamotrygon cf. histrix (Elasmobranchii: Potamotrygonidae), from the Amazon Region, Brazil

Abstract: A haemogregarine is described in 12 cururu stingray (Potamotrygon cf. histrix), from Mariuá Archipelago, Negro River, in the Brazilian Amazon Basin. All animals, both male and female, were parasitized by the haemogregarine and parasitaemia varied between 0.8% and 10% of erythrocytes. The stages observed included trophozoites or merozoites, suspected meronts, and gamonts presumed to be of two types, macrogamonts and microgamonts. Most stages were observed inside mature erythrocytes, while others were extracellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…Differently from the results found by Smit et al (2006) in which the variation in the morphology of the teleost erythrocytes was not observed by response to the presence of parasites, in the P. wallacei, the hemoparasite altered the position of the nucleus, moving it to one of the extremities of the cell. The displacement of the nucleus is probably a result of the greater size that the gametocyte presents in proportion to the volume (>50%) of the red blood cell, these studies were similar to those found by Magro et al (2015).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Differently from the results found by Smit et al (2006) in which the variation in the morphology of the teleost erythrocytes was not observed by response to the presence of parasites, in the P. wallacei, the hemoparasite altered the position of the nucleus, moving it to one of the extremities of the cell. The displacement of the nucleus is probably a result of the greater size that the gametocyte presents in proportion to the volume (>50%) of the red blood cell, these studies were similar to those found by Magro et al (2015).…”
Section: Discussionsupporting
confidence: 77%
“…Recently described in a freshwater stingray (Magro et al, 2015), these parasites can take advantage of temperature fluctuations, reproduction strategies, population genetic patterns, as well as habitat and migratory behavior to reproduce and proliferate in the blood of a diversity of hosts (Davies and Johnston, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Additional coccidian blood parasites known to infect chondrichthyans are species of Haemogregarina Danilewsky, 1885 (Haemogregarinidae) (e.g. Aragort et al 2005, Magro et al 2016. Few studies reported haemogregarines from marine teleost fishes from South Africa (Fantham 1930, Smit and Davies 1999, 2001, Smit et al 2003, Hayes et al 2006, Ferreira et al 2012.…”
Section: Parasite Groups Infecting Chondrich-thyansmentioning
confidence: 99%
“…They have great socioeconomic importance, especially because of their use in the international ornamental sh trade, and because they represent an alternative source of income for riverine communities living along the tributaries of the middle Rio Negro basin (Chao et al 2001). There is a relationship of freshwater stingrays with shermen, especially by the presence of stingers that can cause accidents (Oliveira et al 2015). Four valid species are found in this black water system: Potamotrygon motoro (Müller & Henle 1841), Potamotrygon orbignyi (Castelnau 1855), Potamotrygon schroederi (Fernández-Yépez 1958) and Paratrygon aiereba (Müller & Henle 1841).…”
Section: Introductionmentioning
confidence: 99%